2017
DOI: 10.1103/physreva.96.033606
|View full text |Cite
|
Sign up to set email alerts
|

Optical lattices as a tool to study defect-induced superfluidity

Abstract: We study the superfluid response, the energetic and structural properties of a one-dimensional ultracold Bose gas in an optical lattice of arbitrary strength. We use the Bose-Fermi mapping in the limit of infinitely large repulsive interaction and the diffusion Monte Carlo method in the case of finite interaction. For slightly incommensurate fillings we find a superfluid behavior which is discussed in terms of vacancies and interstitials. It is shown that both the excitation spectrum and static structure facto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 52 publications
3
10
0
Order By: Relevance
“…Recently, a preprint appeared reporting the numerical study of the Mott-U transition with results consistent with ours [49].…”
supporting
confidence: 85%
“…Recently, a preprint appeared reporting the numerical study of the Mott-U transition with results consistent with ours [49].…”
supporting
confidence: 85%
“…The gas in this phase therefore represents a momentum delocalized superfluid that exhibits some of the distinct characteristics of both the superfluid and the pinned phase. The observed momentum distribution is similar to the momentum distributions found in supersolids [52] and it has recently been suggested that the incommensurate phase of the TG gas in deep lattices is similar to a defect-induced superfluid phase and can be utilized to investigate the Andreev-Lifschitz-Chester mechanism [12,53].…”
Section: Coherence and Momentum Distributionsupporting
confidence: 74%
“…If the deviation from the commensurate phase at F=1 is microscopic, such that N=M±1, the phase becomes gapless with a quadratic dispersion relation. On the other hand, for a macroscopic number of defects, such as N=M±M/2, the phase is also gapless, but with a linear dispersion relation [12]. These regimes are, however, continuously connected which can be seen in figure 4(a), where the momentum distribution as a function of F is plotted for a constant depth = V E 20 r 0 .…”
Section: Coherence and Momentum Distributionmentioning
confidence: 98%
See 1 more Smart Citation
“…4 indicate the strong rotonization of the collective excitation branch near the phase transition. By introducing a small fraction of vacancies one can expect the formation of a quadrupolar supersolid in the strongly interacting regime [38], which is similar to the vacancy-induced Andreev-Lifshitz mechanism [70][71][72][73][74].…”
mentioning
confidence: 92%